Documentation for the COVID-19 food trade policy tracker: Tracking government responses affecting global food markets during the COVID-19 crisis - Laborde Debucquet, David; Mamun, Abdullah; Parent, Marie (International Food Policy Research Institute, 2020)
In response to the COVID-19 crisis, some governments have implemented export restrictions and other trade policy measures to secure their food supply. This behavior can increase global food prices, with consequences including the exacerbation of hunger and income losses for producers in export-restrict-ing countries. Intergovernmental organizations and other actors need current information on food trade policy to curb detrimental reactive policy and enable cooperation. To address this need, we provide the COVID-19 Food Trade Policy Tracker. Gathering data from sources including the media, national gov-ernments, expert input, the OECD, and the IMF, we provide up-to-date information on food trade poli-cies implemented during the COVID-19 crisis and the likely magnitude of their effects.